Does the marine functioning link with the supply of ecosystem services and human benefits? A practical application in the Bay of Biscay - Olano-Arbulu, Aitziber; Uyarra, María C.; Pouso, Sarai; Borja, Angel (Frontiers in Marine Science, 2025)
Marine ecosystem services provide multiple benefits and hold significant economic value; however, the capacity of the marine environment to provide ecosystem services can be compromised by anthropogenic pressures. To ensure proper environmental conditions and human well-being, it is necessary to study the functioning of marine ecosystem services. In this context, the aim of this study is to test whether the Common International Classification of Ecosystem Services (CICES) cascade framework is adequate to explain the flow between the natural and the socio-economic domains and identify its limitations. To this end, the study was divided in two parts: (i) review, compilation and classification of CICES Ecosystem Services Cascade model indicators, for three marine ecosystem service examples (provisioning, regulation and maintenance, and cultural), together with the analysis of the number of indicators and the match of the classification undertaken by the authors in the literature and CICES proposal; and (ii) the application of the CICES Ecosystem Services Cascade model to the practical case study of the anchovy fishery in the Bay of Biscay. The results obtained show that many indicators were incorrectly assigned in the literature to the different components of the CICES Ecosystem Services Cascade model. This study highlights the need to develop a standardized classification and understanding of the marine ecosystem services. Significant correlations between the different five steps of the CICES Ecosystem Services Cascade model were obtained, suggesting that this cascade is effective at explaining the links between a healthy environment and the sustainable supply of ecosystem services and benefits.